2010
DOI: 10.3102/0013189x09357621
|View full text |Cite
|
Sign up to set email alerts
|

The Achievement Gap and the Discipline Gap

Abstract: The gap in achievement across racial and ethnic groups has been a focus of education research for decades, but the disproportionate suspension and expulsion of Black, Latino, and American Indian students has received less attention. This article synthesizes research on racial and ethnic patterns in school sanctions and considers how disproportionate discipline might contribute to lagging achievement among students of color. It further examines the evidence for student, school, and community contributors to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
682
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,013 publications
(706 citation statements)
references
References 65 publications
19
682
0
5
Order By: Relevance
“…Moreover, a Department of Education report based on statistics from 72,000 schools in 7,000 school districts across the country found that although African American students accounted for 35% of those suspended once and 39% of all expulsions, they made up only 18% of those enrolled (Gregory, Skiba, & Noguera, 2010;Koon, 2013). Restorative justice programs represent one increasingly popular movement intended to improve school climates, thereby reducing peer violence and aggression (Morrison, 2007).…”
Section: Daniel B Neillmentioning
confidence: 99%
“…Moreover, a Department of Education report based on statistics from 72,000 schools in 7,000 school districts across the country found that although African American students accounted for 35% of those suspended once and 39% of all expulsions, they made up only 18% of those enrolled (Gregory, Skiba, & Noguera, 2010;Koon, 2013). Restorative justice programs represent one increasingly popular movement intended to improve school climates, thereby reducing peer violence and aggression (Morrison, 2007).…”
Section: Daniel B Neillmentioning
confidence: 99%
“…However, this study did not examine exclusionary sanctions like suspension, nor did it provide a comparison with a traditional school. While several studies have been conducted to compare academic achievement in Montessori and non-Montessori environments (Dohrmann et al, 2007;Lillard & ElseQuest, 2006;Lopata, Wallace, & Finn, 2005), there is a need for research on discipline outcomes in Montessori settings because discipline and achievement are inextricably linked (Gregory et al, 2010). Various studies have evaluated the academic benefits of Montessori for students of color (Ansari & Winsler, 2014;Lopata et al, 2005;Rodriguez, Irby, Brown, Lara-Alecio, & Galloway, 2005), but none have examined discipline for students of color in Montessori schools.…”
Section: Montessori Behavior and Disciplinementioning
confidence: 99%
“…Indeed, racially disparate use of exclusionary discipline, like suspension and expulsion, does result in unequal opportunities to learn. Gregory, Skiba, and Noguera (2010) even refer to the achievement gap and the "discipline gap" as "two sides of the same coin" (p. 59). Though some scholars have begun to advocate for alternatives to suspension, such as restorative justice (Gonzalez, 2015) or PBIS (Vincent et al, 2015), out-of-school suspension remains a widespread school response to student misbehavior.…”
Section: Negative Effects Of Out-of-school Suspensionmentioning
confidence: 99%
“…Although the research cited above occurred many years ago, the storyline in the empirical literature remains relatively consistent: students of color and those from lower socioeconomic backgrounds still disproportionately receive harsher exclusionary practices (see, for instance, Gregory, Skiba, & Noguera, 2010;Lewis, Butler, Bonner, Fred, & Joubert, 2010;Skiba et al, 2011). Why are students of color and those from lower socioeconomic backgrounds punished more severely and frequently?…”
mentioning
confidence: 99%